2013
DOI: 10.1038/nn.3467
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic binding of transcription factors to cell-specific enhancers programs motor neuron identity

Abstract: Efficient transcriptional programming promises to open new frontiers in regenerative medicine. However, mechanisms by which programming factors transform cell fate are unknown, preventing more rational selection of factors to generate desirable cell types. Three transcription factors, Ngn2, Isl1 and Lhx3, were sufficient to program rapidly and efficiently spinal motor neuron identity when expressed in differentiating mouse embryonic stem cells. Replacement of Lhx3 by Phox2a led to specification of cranial, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
257
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(289 citation statements)
references
References 50 publications
15
257
2
Order By: Relevance
“…This and our conditional knockout results point to ISL1 being a terminal differentiation gene that is necessary to establish the specific identity of POMC neurons after these cells are born and accumulate in the mantle zone, giving rise to the arcuate nucleus. Recent work has shown that Isl1 plays pivotal roles in determining the cell fate of GABAergic medium spiny striatofugal neurons (40), cholinergic magnocellular striatal interneurons (41), and cholinergic spinal and cranial motor neurons (42). Interestingly, these different ISL1-dependent neuronal types participate in pyramidal and extrapyramidal circuits that coordinate body movement and locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…This and our conditional knockout results point to ISL1 being a terminal differentiation gene that is necessary to establish the specific identity of POMC neurons after these cells are born and accumulate in the mantle zone, giving rise to the arcuate nucleus. Recent work has shown that Isl1 plays pivotal roles in determining the cell fate of GABAergic medium spiny striatofugal neurons (40), cholinergic magnocellular striatal interneurons (41), and cholinergic spinal and cranial motor neurons (42). Interestingly, these different ISL1-dependent neuronal types participate in pyramidal and extrapyramidal circuits that coordinate body movement and locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…To identify novel regulators of motor axon pathfinding that function downstream of the ISL1-LHX3 complex, we analyzed genome-wide ISL1-LHX3-bound genomic loci mapped by ChIP-seq analyses (Lee et al, 2013;Mazzoni et al, 2013). Bioinformatics analysis of these ChIP-seq datasets led us to identify a series of putative direct MN target genes of the ISL1-LHX3 complex (data not shown).…”
Section: Identification Of Isl1-lhx3 Complex-binding Sites In the Stamentioning
confidence: 99%
“…To understand better the role of the ISL1-LHX3 complex in spinal MN specification and differentiation, a genome-wide mapping of ISL1-LHX3 complexbinding sites has been recently performed using chromatin immunoprecipitation sequencing (ChIP-seq) (Lee et al, 2013;Mazzoni et al, 2013). These studies, combined with MN transcriptome analyses (Lee et al, 2012;Mazzoni et al, 2013), revealed that the ISL1-LHX3 complex directly regulates the expression of a wide range of downstream effector genes that function not only in cell fate specification but also in subsequent maturation steps of MN differentiation, such as cell migration, axon pathfinding and synapse formation. As a result, the roles of individual target genes of the ISL1-LHX3 complex in MN specification and differentiation/maturation have finally begun to be dissected (Cho et al, 2014;Lee et al, 2012Lee et al, , 2013Mazzoni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIPs were carried out as previously described 57 with the following modifications: A) Differentiated EBs were collected, washed with PBS and then dissociated with Accutase (Gibco) enzyme for 3 minutes. After spin down, single-cell suspension were fixed in fixation buffer (11% freshly added formaldehyde / 0.1M NaCl/1mM EDTA/50mM HEPES-KOH pH 7.6) containing 1% formaldehyde for 15 min at room temperature and quenched with 0.125 M Glycine for additional 5 min at room temperature.…”
Section: Chromatin Immunoprecipitationsmentioning
confidence: 99%